2016
DOI: 10.3389/fpls.2016.00423
|View full text |Cite
|
Sign up to set email alerts
|

Functional Update of the Auxiliary Proteins PsbW, PsbY, HCF136, PsbN, TerC and ALB3 in Maintenance and Assembly of PSII

Abstract: Assembly of Photosystem (PS) II in plants has turned out to be a highly complex process which, at least in part, occurs in a sequential order and requires many more auxiliary proteins than subunits present in the complex. Owing to the high evolutionary conservation of the subunit composition and the three-dimensional structure of the PSII complex, most plant factors involved in the biogenesis of PSII originated from cyanobacteria and only rarely evolved de novo. Furthermore, in chloroplasts the initial assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 111 publications
0
35
0
Order By: Relevance
“…CP43 incorporates into RC47 and is followed by an association of extrinsic oxygen-evolving complexes. Finally, in green plants, the PSII core complex dimerizes and binds to LHCII to form PSII supercomplexes (Komenda et al, 2012;Nickelsen and Rengstl, 2013;Plochinger et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…CP43 incorporates into RC47 and is followed by an association of extrinsic oxygen-evolving complexes. Finally, in green plants, the PSII core complex dimerizes and binds to LHCII to form PSII supercomplexes (Komenda et al, 2012;Nickelsen and Rengstl, 2013;Plochinger et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Transcription factor Pur‐alpha 1 specifically binds the purine‐rich double‐stranded telomeric repeated sequence 5′‐AAACCCTAA‐3′ found in promoter telo boxes (Tremousaygue, Manevski, Bardet, Lescure, & Lescure, ) and the ethylene‐responsive transcription factor RAP2‐12. Finally, mostly the protein and enzyme genes, such as photosystem II core complex proteins psbY (Plochinger, Schwenkert, Sydow, Schroder, & Meurer, ), protein phytochrome kinase substrate 4 (PKS4) (Fankhauser & Christie, ), and light‐inducible protein CPRF2, participate in the light reaction (Monir & Zhu, ). Abscisic acid‐insensitive 5‐like protein 1 (Wang, Li, Mao, Li, & Jing, ), ethylene‐responsive transcription factor RAP2‐12 (Kosmacz et al, ), auxin‐induced protein AUX28‐like (Xie et al, ), and auxin‐induced protein 22D‐like (Han et al, ) take part in plant growth and development regulated by plant hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic inspections and alignments of the psbY amino acid sequence revealed that the protein is present in all photosynthetic plants, in some algal chloroplasts (formerly ycf32) and also in various cyanobacteria (formerly identified as psbY, ycf32 or Sml0007) (Gau et al, 1998). In higher plants, psbY is nuclear-encoded and targeted to the thylakoids (Plöchinger et al, 2016). Four genes, chlB, I, L, N, are conserved as well as 11 small hydrophobic proteins (psbH, I, J, K, L, M, T, X, Y, Z and ycf12) involved in photosynthesis that are well conserved from Cyanobacteria (Inoue-Kashino et al, 2011) to higher plants (Shi & Schroder, 2004;Kashino et al, 2007;Iwai et al, 2010).…”
Section: Gene Contentmentioning
confidence: 99%